Development Of e Module Based Blended Learning On Hadith Material About Intention In Madrasah Ibtidaiyah - Dani Cahyani Rahayu; Abdulloh Hamid; Mohammad Salehuddin; Winarto Eka Wahyudi (Universitas Yudharta Pasuruan, 2020)
This study aims to develop a blended learning-based e modulon the hadith material about intentions at the madrasah ibtidaiyah or elementary education level. This study uses the research and development method (Research and Development) with the ADDIE or Analyze development model, Design, Development, Implementation, and Evaluate. The moduldeveloped is made using the Kvisoft Flipbook Maker application and published in Html format, which can be accessed via the internet network. The developed blended learningcombines face-to-face learning and distance learning as the learning process occurs, especially during the pandemic and the new normal. E modulis used as a companion to teaching materials that can stimulate students to study independently due to the parents' busyness or the teacher's distance, which makes the obligation to study independently echoed together with the independent campaign in learning. The validity and response tests carried out 85% agreed with the use of e moduland the pretest and posttest test of students' learning outcomes also showed the effectiveness of using the blended learning-based e modulwith an average of 87 out of 20 students who became respondents.